Single and mixture toxicities of BDE-47, 6-OH-BDE-47 and 6-MeO-BDE-47 on the feeding activity of Daphnia magna: From behavior assessment to neurotoxicity. (March 2018) - Liu, Yanhua; Guo, Ruixin; Tang, Shengkai; Zhu, Fengyi; Zhang, Shenghu; Yan, Zhengyu; Chen, Jianqiu
Abstract: Although 2, 2′, 4, 4′-tetrabrominated diphenyl ether (BDE-47), 6-hydroxy-2, 2′, 4, 4′-tetrabromodiphenyl ether (6-OH-BDE-47) and 6-methoxy-2, 2′, 4, 4′-tetrabromodiphenyl ether (6-MeO-BDE-47) clearly disrupt the endocrine system, current knowledge of their single and/or mixture toxicities on other behaviors of aquatic organisms remains limited. In the present study, Daphnia magna was used to investigate the single and mixture toxicities of BDE-47, 6-OH-BDE-47 and 6-MeO-BDE-47 as measured by inhibition of feeding during exposure and post-exposure periods. Additionally, the biochemical performance, i.e., the activities of super oxidase dismutase (SOD), glutathione peroxidase (GPx) and acetylcholinesterase (AChE) of the test organism was studied to investigate the potential mechanisms of the toxicity of the target compounds. The three target compounds produced an obvious depressive effect on feeding behavior during the exposure period, and the effect increased with increasing concentrations. D. magna was most sensitive to 6-OH-BDE-47. The toxicity of the ternary mixture showed an obvious concentration-dependent effect, whereas the binary mixture toxicity showed the characteristics of hormesis. During the post-exposure period, overcompensation occurred, indicating a short-term effect of the target compounds on D. magna . Additionally, significant changes occurred in neurological responses, indicating that these compounds might have neurobehavioral toxicity in D. magna . The decrease in oxidative stress enzymes (SOD and GPx) indicated that the antioxidant response of D. magna was destroyed. Graphical abstract: Highlights: BDE-47, 6-OH-BDE-47 and 6-MeO-BDE-47 have neurotoxic effects on D. magna. A concentration-dependent effect was shown in single and mixture toxicity assays. An overcompensation of the feeding behavior occurred after exposure. The antioxidant and neurological responses were destroyed in the exposure period.